1989
DOI: 10.1164/ajrccm/140.6.1734
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fiberoptic Bronchoscopy to Retrieve Bronchial Foreign Bodies in Adults

Abstract: The flexible fiberoptic bronchoscope was used to treat bronchial foreign bodies in 33 adults. The length of time that the foreign body was in the lung was less than 1 wk in six (acute group), more than 1 month in 21 (chronic group), and uncertain in two (uncertain group), and the foreign body was an endogenous broncholith in four patients (broncholith group). The foreign bodies were nonfragile, solid matter in most cases and they frequently had sharp projections on them. Granulations around the foreign body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 6 publications
1
31
0
1
Order By: Relevance
“…The result was much better than in that experienced by LIMPER and PRAKASH [8], and could have reached the success rate of rigid open tube bronchoscopy if the duration of the foreign body in the airway was considered. The improved and modified technique for retrieving foreign bodies has been published in detail elsewhere [27].…”
Section: Discussionmentioning
confidence: 99%
“…The result was much better than in that experienced by LIMPER and PRAKASH [8], and could have reached the success rate of rigid open tube bronchoscopy if the duration of the foreign body in the airway was considered. The improved and modified technique for retrieving foreign bodies has been published in detail elsewhere [27].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms that have been most commonly reported include chronic cough and wheeze, recurrent pneumonia and haemoptysis [1][2][3]. Lan et al, reported that 70% of their patients were chronic (defined as presence of the foreign bodies in the airways for more than one month prior to removal), with a mean duration was 20.6 months [8]. In a CxR, the diagnosis and localization of opaque foreign bodies is more straightforward compared to organic foreign bodies which tend to be radiolucent and hence does not show up on CxR.…”
Section: Discussionmentioning
confidence: 99%
“…Overall success rates for retrieval of FBs ranges from 61 to 89% for both flexible and rigid bronchoscopies. (Limper &Prakash, 1990;Debeljak et al, 1999;Cunanan, 1978;Lan et al, 1989) FFB is probably more useful for FB in distal segments beyond the reach of rigid bronchoscope. In some cases, flexible and rigid bronchoscopy are complementary, with FFB assisting in the localization of the FB and then retrieval done with the rigid bronchoscope.…”
Section: Removal Of Foreign Bodiesmentioning
confidence: 99%